Correlation of HER2 with Stages of Carcinoma Stomach (Journal of Surgical Sciences, 2025)
Background: The variability of prognosis within a clinical & pathological stage of gastric cancer, underscores the need for specific biological markers to identify subgroups of patients for intensive treatment. The purpose of this study was to evaluate the correlation between HER2overexpression with different stages of carcinoma stomach. To our knowledge, this is the first study from Bangladeshi population reporting on the relationship of HER-2 expression with different stages of carcinoma stomach.Methods: This cross-sectional study included 53 patients with gastric cancer who underwent surgery at different Hospital in Dhaka city between November 2016 and October 2017. All the patients were clinically staged before surgery & tumor samples were examined for HER2 expression by immunohistochemistry (IHC). The results correlated with clinicopathological features & stages of carcinoma stomach. Percentage expression for positivity of HER2 was estimated along with 95% confidence interval. The differences in the positivity rate between different sex, stages and grades were tested through ‘Chi’ square test of significance and a value of p 0.05) were found betweenHER-2 positive group with age, gender and tumor location. More than three fourth (80.0%) patients had intestinal type and 2(20.0%)had diffuse type histological pattern in HER2 positive group, which was statistically significant (p